2008
DOI: 10.1136/jnnp.2008.154799
|View full text |Cite|
|
Sign up to set email alerts
|

A practical approach to acute vertigo

Abstract: Patients complaining of symptoms of acute vertigo present a diagnostic challenge for the clinician; the main differential diagnoses are acute unilateral peripheral vestibulopathy ("vestibular neuritis"), cerebellar stroke or migraine. The head impulse test is useful in the acute situation because, of these three diagnostic alternatives, it will only be positive in patients with vestibular neuritis. A history of acute vertigo and hearing loss suggests Ménière's disease but the clinician must be wary of anterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 53 publications
1
30
0
1
Order By: Relevance
“…A careful history is the most important part of a medical examination for vertigo, especially to establish whether it is acute, chronic or recurrent [2]. ER practice deals with the acute vertigo of which the main differential diagnoses are acute unilateral peripheral vestibulopathy ("vestibular neuritis"), cerebellar stroke or migraine [3]. This study has been planned to figure out the frequency of the emergent neurological diagnoses in patients who admitted to ER with vertigo in a state hospital in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…A careful history is the most important part of a medical examination for vertigo, especially to establish whether it is acute, chronic or recurrent [2]. ER practice deals with the acute vertigo of which the main differential diagnoses are acute unilateral peripheral vestibulopathy ("vestibular neuritis"), cerebellar stroke or migraine [3]. This study has been planned to figure out the frequency of the emergent neurological diagnoses in patients who admitted to ER with vertigo in a state hospital in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Criteria for neuroimaging in acute vertigo is the presence of vertigo plus one or more of the following: 13 • new onset headache • central neurological symptoms or signs…”
Section: When Is Neuroimaging Indicated?mentioning
confidence: 99%
“…It can be helpful to ask a patient if the problem is 'in their legs or in their head' (spinal cord/cerebellar v. vestibular causes) or if they feel 'as if they are about to faint' (presyncope). [3] Recent studies, however, have shown that the timing (especially duration) and triggers of symptoms of dizziness may be more helpful in diagnosing the underlying disorder than the quality of the symptoms. [4] Determining whether vertigo is episodic or persisting, or provoked by positional changes, is very helpful for the diagnosis.…”
Section: Clinical Approach To a Patient With Acute Vertigo Is It Vertmentioning
confidence: 99%
“…with visual fixation) suggests intact central mechanisms. [3] The vestibular ocular reflex is impaired in peripheral vestibular disorders, and thus the head impulse (or head thrust) test will be abnormal. This test is fairly easy to perform, and is particularly useful to confirm peripheral dysfunction.…”
Section: Is the Lesion Central Or Peripheral?mentioning
confidence: 99%
See 1 more Smart Citation